Guided-Wave Up-Conversion Luminescence in Er3+/Yb3+ Co-doped Phosphate Glass Waveguide Produced by Direct Femtosecond Laser Writing - Zhou, Yuxiang; Cheng, Chen; Hu, Lili; Chen, Feng (Frontiers in Physics, 2022)
We report on guided-wave up-conversion luminescence in femtosecond laser writing cladding waveguides in Er3+/Yb3+ co-doped phosphate glass. The waveguides were fabricated with 20-μm- and 100-μm-diameter of the guiding cores. The guiding properties of waveguides have been investigated at 633nm by end face coupling of free space light and physical contact of fibers. The experimental and calculated results of propagating modal profiles and losses have proved favorable performances suitable to Gaussian mode field and multi-mode applications. Under the optical pump laser at 980 nm, the guided-wave up-conversion luminescence at visible light range has been realized through the waveguides.